2022
DOI: 10.1097/jac.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perception of Patient Safety Culture in Primary Care During the COVID-19 Pandemic

Abstract: Investigation of nurses' perceptions of patient safety culture (PSC) might be beneficial in identifying safety areas that need improvement, especially during the COVID-19 pandemic. The study reports on the PSC in primary care from the nurses' perspective during the pandemic. Nurses (n = 117) evaluated teamwork (87.3%) and staff training (80.9%) positively but work pressure and pace (26.1%) and patient care tracking (45.3%) concerning PSC dimensions negatively. Limited care coordination and continuity lead to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…We did not find similar reports in the literature to support our research data probably because the issue of intention to report a near-miss event is not widely published in general, particularly not during the COVID-19 crisis. However, this finding is similar to results in other studies that examined perception of patient safety culture during COVID-19 14,16,17. Some of the data are also consistent with studies completed before COVID-19.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We did not find similar reports in the literature to support our research data probably because the issue of intention to report a near-miss event is not widely published in general, particularly not during the COVID-19 crisis. However, this finding is similar to results in other studies that examined perception of patient safety culture during COVID-19 14,16,17. Some of the data are also consistent with studies completed before COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…However, this finding is similar to results in other studies that examined perception of patient safety culture during COVID-19. 14,16,17 Some of the data are also consistent with studies completed before COVID-19. Both Toren et al 3 and Aka-Zohar et al 2 found that teamwork between hospital departments predicted the intention to report a near-miss event.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Students who had experience with adverse events (or their reporting) evaluated their knowledge, skills and/or attitudes towards patient safety significantly better (e.g., Firat Firat Kılıç and Cevheroğlu, 2023; (Fisher and Kiernan, 2019). The quantitative study revealed that the current clinical placement can also affect the perception of patient safety, with students from intensive care units and primary care settings evaluating selected dimensions of patient safety better (Kalánková et al, 2022). Behaviour related to patient safety, as well as lower student workload, also had an impact on the perception of patient safety (Kong et al, 2019).…”
Section: Factors Related To the Clinical Environmentmentioning
confidence: 99%